Night Journey - Negroni, María, 1951- (Book collections on Project MUSE., 2002)
One of South America's most celebrated contemporary poets takes us on a fantastic voyage to mysterious lands and seas, into the psyche, and to the heart of the poem itself. Night Journey is the English-language debut of the work that won María Negroni an Argentine National Book Award. It is a book of dreams--dreams she renders with surreal beauty that recalls the work of her compatriot Alejandra Pizarnik, with the penetrating subtlety of Borges and Calvino. In sixty-two tightly woven prose poems, Negroni deftly infuses haunting imagery with an ironic, personal spirituality. Effortlessly she navigates the nameless subject to the slopes of the Himalayas, to a bar in Buenos Aires, through war, from icy Scandinavian landscapes to the tropics, across seas, toward a cemetery in the wake of Napoleon's hearse, by train, by taxis headed in unrequested directions, past mirrors and birds, between life and death. Night Journey reflects a mastery of a traditional form while brilliantly expressing a modern condition: the multicultural, multifaceted individual, ever in motion. Displacement abounds: a "medieval tabard" where a pelvis should be, a "lipless grin," a "beach severed from the ocean." In one poem "nomadic cities" whisk past. In another, smiling cockroaches loom in a visiting mother's eyes. Anne Twitty, whose elegant translations are accompanied by the Spanish originals, remarks in her preface that the book's "indomitable literary intelligence" subdues an unspoken terror--helplessness. Yet, as observed by the angel Gabriel, the consoling voice of wisdom, only by accepting the journey for what it is can one discover its "hidden splendor," the "invisible center of the poem." As readers of this magnificent work will discover, this is a journey that, because its every fleeting image conjures a thousand words of fertile silence, can be savored again and again.